Influence of eco-innovation on Indian manufacturing sector sustainable performance - Ganapathy, Satish Pandian; Natarajan, Jawahar; Gunasekaran, Angappa; Subramanian, Nachiappan (Taylor & Francis, 2014)
Manufacturing firms are striving to improve their sustainable performance in order to satisfy multiple stakeholders. Eco-innovation is a promising approach that decreases environmental impact and helps firms to increase their business value. There are several antecedents which help the firms to innovate and improve their triple bottom line performance. Among the antecedents, management and innovative practices are directly related to eco-innovation. It is not well known what practices and innovations help the firms to eco-innovate as well as to improve sustainable performance. Hence, the research objective of this paper is to identify the suitable combination of management and innovative practices that help firms to eco-innovate as well as to achieve overall sustainable performance. The paper develops an eco-innovation conceptual model which relates the management and innovative practices (antecedents) and overall sustainable performance (consequences) of eco-innovation using institutional theory. Using Indian manufacturing sector’s empirical data and Structural Equation Modelling (SEM) approach, this paper determines the effect of eco-innovation’s antecedents and consequences. In the Indian context, this study suggests that the role of management practice is more significant towards eco-innovation than innovative practices. The results reflect practitioners’ view on how to increase innovation rate and to focus more on social aspects. The finding suggests that training on environmental related practices could tackle innovation and social aspects in the Indian manufacturing sector context.